Plum in the economy of Bosnia and Herzegovina (1861-1918) - Užičanin, Salkan (Historical Thought, 2025)
Few products, which today seem so marginal, had capital importance for national well-being and the country's economy like plums. Bosnia and Herzegovina had particularly favorable climatic and pedological features for plum cultivation. These natural benefits and the multiple possibility of exploitation have enabled the plum to take a dominant place among Bosnian fruits. Its economic importance did not go unnoticed by the Ottoman and later Austro-Hungarian authorities, who paid special attention to it. Therefore, it should not be surprising that in the observed period the plum was a kind of national treasure, and plum growing was the most developed branch of fruit growing. The Austro-Hungarian occupation authorities especially improved the method of processing and the sale of plums and contributed to its becoming an important economic branch.